Reductions in connectivity and habitat quality drive local extinctions in a plant diversity hotspot. Issue 6 (8th August 2015) - Hooftman, Danny A. P.; Edwards, Bryan; Bullock, James M.
Abstract : It is well documented that habitat loss is a major cause of biodiversity decline. However, the roles of the different aspects of habitat loss in local extinctions are less understood. Anthropogenic destruction of an area of habitat causes immediate local extinction but subsequently three additional gradual drivers influence the likelihood of delayed extinction: decreased habitat patch size, lower connectivity and habitat deterioration. We investigated the role of these drivers in local extinctions of 82 declining species in a UK biodiversity hotspot. We combined a unique set of ≈ 7000 vegetation surveys and habitat maps from the 1930s with contemporary species' occurrences. We extrapolated from these surveys to the whole 2500‐km 2 study area using habitat suitability surfaces. The strengths of drivers in explaining local extinctions over this 70 yr period were determined by contrasting connectivity, patch size and habitat quality loss for locations at which a species went extinct and those with persisting occurrences. Species' occurrences declined on average by 60%, with half of local extinctions attributable to immediate habitat loss and half to the gradual processes causing delayed extinctions. On average, locations where a species persisted had a 73% higher contemporary connectivity than those suffering extinctions, but showed no differences in historical connectivity. Furthermore, locations with extinctions experienced a 37% greater decline in suitability associated with changes in habitat type. The strength of the drivers and the proportion of extinctions depended on the species' habitat specialism, but were affected only minimally by life‐history characteristics. In conclusion, we identified a hierarchy of drivers influencing local extinction: with connectivity loss being the strongest, suitability change being moderately important, but changes in habitat patch size having only weak effects. We suggest conservation efforts could be most effective by strengthening connectivity along with reducing habitat deterioration, which would benefit a wide range of species.